Sesquiterpene Lactones as Potential Cyclin B1/CDK1 Complex Inhibitors: Sesquiterpene Lactones as Potential Cyclin B1/CDK1 - Zaman, Aqsa; Yousaf, Zoufishan; Gul, Sameena; Ali, Muhammad; Khan, Muhammad (Futuristic Biotechnology, 2023)
Cancer is second most common cause of death globally. Uncontrolled regulation of cell cycle may cause various cancerous anomalies. Objective: To Identify of Sesquiterpene Lactones (SLs) as inhibitors of Cyclin B1 (CB1) and Cyclin Dependent Kinase 1 (CDK1) complex. Methods: Checkpoints proteins (CDK1/CB1) of G2/M phase have been assessed with three SLs (ilicol, eucalyptone and ascleposide E) through molecular docking study. AutoDock Vina (ADV), PyMol version-2.5.2 and BIOVIA Discovery Studio 2021 was used for the visualization of docking analysis. Results: Outcomes of the current investigations reveal that ascleposide E exhibit the highest binding affinity of -7.1 kcal/mol (with inhibition constant of 5.9 µM) with CDK1 and CB1. Both potential complexes have shown good hydrogen bond interactions. Drug likeness of selected drug candidates were validated by ADMET analysis and Lipinski’s rule of 5. Conclusions: Present study concluded that Ascleposide E have greater inhibition potential against CB1/CDK1 protein complex by making hydrogen and hydrophobic interactions. Moreover, this selected compound showed favorable drug likeness profiling. To validate the inhibitory activity of Ascleposide E to greater extent, further in vitro investigations are recommended to develop this compound into novel G2/M phase inhibitors.